2020
DOI: 10.1016/j.ssmph.2020.100686
|View full text |Cite
|
Sign up to set email alerts
|

Cigarette taxes, prices, and disparities in current smoking in the United States

Abstract: Increasing cigarette taxes has been the cornerstone of tobacco control policy. Recent work has argued that raising cigarette taxes alone may no longer be an effective strategy for lowering smoking rates. We largely confirm these findings but also find that increases in price continue to predict lower smoking participation in most model specifications. We argue that raising cigarette prices via taxation remains an effective public health policy. We discuss the advantages of homogeneous tax environments and mini… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 32 publications
1
14
0
Order By: Relevance
“…Specifically, a 1-NIS increase in cigarette prices was linked to 2.0% lower odds of being a current smoker (adjusting for income and covariates). This finding is similar to that found in a study by Kalousova et al in the US, where a 1 dollar increase in local price was associated with 0.6% decrease in current smoking [20]. Levy et al emphasize that large increases in cigarette taxes is the most robust policy lever to reduce smoking alongside other strategies, such as smoke free laws, marketing bans, and media campaigns [21].…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…Specifically, a 1-NIS increase in cigarette prices was linked to 2.0% lower odds of being a current smoker (adjusting for income and covariates). This finding is similar to that found in a study by Kalousova et al in the US, where a 1 dollar increase in local price was associated with 0.6% decrease in current smoking [20]. Levy et al emphasize that large increases in cigarette taxes is the most robust policy lever to reduce smoking alongside other strategies, such as smoke free laws, marketing bans, and media campaigns [21].…”
Section: Discussionsupporting
confidence: 85%
“…Specifically, our results indicate that higher cigarette prices are markedly related to lower odds of current smoking in individuals of moderate and high-income, but not significantly in participants of lowincome. This finding contradicts prior studies reporting that individuals of low-income exhibit greater price sensitivity than their higher income counterparts [20,22]. A study by Sharbaugh et al, however, similarly observed that cigarettes taxes had the least impact on the prevalence of smoking among low-income US adults [23], suggesting that this population might engage in price minimization behaviors, such as the use of roll-your-own cigarettes [24].…”
Section: Discussionmentioning
confidence: 62%
“…Tobacco taxes can help reduce tobacco‐related disparities in cancer occurrence across income groups and among Black men and AI/AN men and women. People with limited incomes are more sensitive to price than higher income populations and quit tobacco at greater rates after a tax increase 183,184 . The potentially positive effects of tobacco taxes in reducing disparities in the burden of tobacco‐related cancers can be even greater if tax revenues are dedicated to tobacco control and other health‐related programs that serve populations of lower SES 185 …”
Section: Future Directions (Next Steps)mentioning
confidence: 99%
“…There are a growing number of studies in the literature investigating the relationship between smoking behaviors and cigarette prices and taxes among adults [4][5][6][7][8][9][10][11][12] and adolescents [13][14][15]. Some studies have found that cigarette tax and price increases have significant impacts on reducing smoking prevalence [5,12,16,17]. Others have reported weak or no statistically significant effects of cigarette prices and taxes on cigarette use [18].…”
Section: Introductionmentioning
confidence: 99%